Factors influencing self-regulatory fatigue in patients undergoing chemotherapy for gynecologic cancer: a cross-sectional study - Lin, Chunhui; Zhang, Fengzhi; Yang, Fangfang; Lin, Yuanting; Tian, Tian; Shi, Kaige; Li, Manman; Li, Xiaoxue (Frontiers in Psychiatry, 2024)
Objective To understand the current status of self-regulatory fatigue among gynecologic cancer chemotherapy patients and explore influencing factors Methods Using convenient sampling, a total of 232 gynecological cancer chemotherapy patients from two tertiary hospitals in Zhengzhou, Henan, China, were selected as study subjects from February 2023 to April 2023. General information questionnaire, Self-Regulatory Fatigue Scale (SRF-S), Strategies Used by People to Promote Health (SUPPH) Scale, Connor-Davidson resilience scale (CD-RISC) and Perceived Social Support Scale (PSSS) were employed for data collection. The data were analyzed using SPSS 26.0 software. Chi-square test and binary logistic regression were executed to explore the correlates of self-regulatory fatigue, the significance level (α) was set at 0.05. Results The self-regulatory fatigue score of the 232 patients was 44 (36, 56). Binary logistic regression analyses revealed significant associations, demonstrating that residing in urban areas (OR=0.241, P=0.015), having no comorbidities (OR=0.158, P=0.015), increased perceived social support (OR=0.937, P=0.001), strong self-efficacy (OR=0.959, P=0.021), and heightened psychological resilience (OR=0.895, P<0.001) acted as protective factors against self-regulatory fatigue (P < 0.05). Conclusion Patients residing in rural areas, having more than two comorbidities, lower self-efficacy and psychological resilience levels, and lower perceived social support are indicative of higher levels of self-regulatory fatigue. Identifying these influencing factors can provide references and support for developing individualized support and intervention measures to improve patients’ physical and mental well-being.